Analisis Faktor-Faktor Yang Mempengaruhi Kualitas Hidup Penyintas Kanker Ginekologi - Ira Sukyati (AKPER Pasar Rebo, 2018)
Cancer has been the leading cause of death worldwide, and most cancer patients have poor quality of life both from the physical and psychological aspects after being diagnosed with cancer. Problems often experienced by survivors of cancer after completion of treatment, in the form of difficulty in adapting to previous life, because of the physical, emotional and psychosocial effects of cancer that does not subside when the patient reaches remission. Efforts to improve the quality of life of survivors of cancer one of them by anticipating physical symptoms and psychological perceived. Quality of life is an important goal in the treatment of cancer and concerns about physical condition, psychological, body image disturbances, and symptoms that can cause distress need to be anticipated to improve the quality of life of patients. The purpose of this study identifies the factors that affect the quality of life survivors of gynecological cancer. This research use cross sectional research design. The number of respondents in this study were 114 people who were outpatient and had done at least one treatment. The results of this study are The results of this study can be found that the history of treatment is the factor that most affect the quality of life survivors gynecological cancer This study recommends the importance of improving communication by providing information related to things that need to be done post-treatment, from the hospital service order. It helps patients easily adapt to the disease and reduce fear and improve quality of life after undergoing cancer modality therapy